Atacamite Cu2Cl(OH)3: A model compound for the S = 1/2 sawtooth chain? - Heinze, L. (2019)
We present a combined experimental and theoretical study of the mineral atacamite Cu2Cl(OH)3.Based on ab initio band structure calculations, we derive a magnetic coupling scheme of essentially a S = 1/2 sawtooth chain. Experimentally, we fully characterize the long-range antiferromagnetically ordered state and field-induced behavior, here for H k b axis. Magnetic order is suppressed by magnetic fields of ∼ 20 T, while beginning at 31.5 T we observe a wide magnetization plateau at half of the saturation magnetization, Msat/2. Numerical calculations for the magnetization M(H) of the quantum sawtooth chain reveal a plateau at Msat/2, raising the issue of the understandingof its microscopic nature.